Caracterização mecânica de uma porcelana de aplicação convencional e uma prensada para recobrimento de infraestruturas de zircônia e o efeito do método de resfriamento na resistência à flexão biaxial do conjunto zircônia/porcelana - Longhini, Diogo [UNESP] (2014)
This study characterized mechanically a conventional and a pressed feldspathic porcelain indicated for zirconia core in terms of biaxial flexural strength, fracture toughness, Vickers hardness. In addition it was investigated the effect of the glaze cooling rate on the biaxial flexural strength of the zirconia/porcelain bilayer. Specimens monolayers of Vita VM9 (n=15) and Vita PM9 (n=15) (12.0 mm diameter x 1.2 mm thickness) were prepared according to manufacturer’s recommendations for the biaxial flexural strength test (MPa). Afterwards, one fragment of each broken specimen was randomly selected for Vickers hardness measurements (n=15) (VHN). Apparent fracture toughness (MPa.m½) was determined by Vickers hardness indentation technique (n=15). For the biaxial flexural strength of bilayers, zirconia discs (Vita In-Ceram YZ) were veneered with the conventional porcelain Vita VM9 (n=30) or with the pressed porcelain Vita PM9 (n=30). After the glaze firing simulation, the specimens were submitted to fast (n=15) or slow cooling method (n=15). After the biaxial flexural test, the specimens were analyzed in relation to fracture pattern. T-Student tests were performed for the monolayer specimens, while two-way ANOVA (porcelain and cooling method) was used for the bilayer ones (α=.05). Vita PM9 exhibited significantly higher biaxial flexural strength (p<0.01) and hardness than VM9 (p=0.017). However, there was no significant difference (p= 0.41) in fracture toughness between the porcelains. The two-way ANOVA indicated significance only for the porcelain, with superiority for the combination Vita PM9/zirconia (p<0.01).The pressed porcelain seems to be a mechanically more effective alternative for zirconia veneering than the conventional one.